The Design and development of a health communication campaign plan to promote diarrhea prevention and management behaviors among parents and primary child-caregivers of Brgy. Toril Proper, Davao City - Tupas, Trisha S. (2023)
Good health has always been a key element in building a productive society, however, there is a looming crisis particularly posing a grave threat for low- to middle-income countries like the Philippines, that is diarrhea. Diarrhea is a common disease that can be easily prevented and treated, however it is still persistent in killing billions worldwide (Moore, 2015). In Davao Region, there have been numerous diarrhea outbreak that occurred in 2022 alone. This study then, aimed to design and develop a health communication campaign plan to promote diarrhea prevention and management behaviors among parents and primary child-caregivers of Brgy. Toril Proper, Davao City. This study utilized a sequential explanatory mixed-method approach anchored in the theory of Health Belief Model. The quantitative data revealed that the target audience have high existing knowledge, prior exposure and practices, and ideal risk perception scores. It was also revealed that educational attainment, existing knowledge, and perceived severity influences the other variables of this study. The qualitative data on the other hand, revealed the knowledge gaps between community health experts and local officials when it comes to health communication. Also, it was revealed that the residents engage in unguided medication and self-diagnosing behavior which resulted in more negative outcomes during the 2022 diarrhea outbreak in the locale. This albeit having available diarrhea prevention messages. Thus, a health communication campaign plan entitled ?Nay, dali ra ang depensa kontra diarrhea? was developed. The campaign plan was guided by the SBCC framework. Social marketing principles were also explored in identifying the communication strategies, tailored from the identified problems extracted from the formative evaluation.